Mini-enthesitis can differentiate rheumatoid arthritis from psoriatic arthritis: A comprehensive comparative ultrasound study of the joints and mini-entheses of the hands - Tanya Sapundzhieva,; Lyubomir Sapundzhiev,; Anastas Batalov, (Archives of Rheumatology, 2025)
Objectives: This study aimed to explore whether hand ultrasonography (USG) could differentiate between rheumatoid arthritis (RA) and psoriatic arthritis (PsA) patients. Patients and methods: A comprehensive USG of 35 PsA patients (13 males, 22 females; mean age: 60.9±8.4 years; range, 53 to 69 years), 30 RA patients (10 males, 20 females; mean age: 58.4±10.0 years; range, 50 to 61 years), and 20 healthy controls (5 males, 15 females; mean age: 55.6±5.8 years; range, 50 to 61 years) was performed with assessments of the wrist, tendons, mini-entheses, and joints of the second and third finger, both on gray scale and power Doppler USG. Results: Two hundred forty-five joints of PsA patients, 210 joints of RA patients, and 120 joints of healthy controls were assessed by USG. Wrist joint synovitis and tenosynovitis of the extensor digitorum communis and extensor carpi ulnaris tendon were significantly more common in RA patients compared to PsA patients (p<0.001), detected in 93.30%, 63.30%, and 73.30% versus 57.10%, 14.30%, and 2.90%, respectively. The incidence of tenosynovitis of the flexor tendons at the wrist level was significantly higher in RA patients (p=0.003), detected in 36.70% versus 14.30%. Paratenonitis of the finger extensor tendon at the metacarpophalangeal joints was significantly more prevalent in PsA patients, detected in 85.70% versus 3.30% (p<0.001). Central slip enthesitis at the proximal interphalangeal joint and enthesitis of the distal slip of the extensor tendon at the second and third distal phalanx were exclusively found in PsA patients, occurring in 45.70%, 91.40%, and 71.30%, respectively (p<0.001). Flexor tenosynovitis and pseudotenosynovitis were significantly more prevalent in PsA patients (65.70% and 57.10%, respectively) compared to RA patients (16.70% and 0.00%, respectively; p<0.001). PsA patients had significantly higher thickness of the A1 pulley compared to RA patients (p<0.001). Conclusion: Mini-enthesitis is a hallmark USG finding in PsA.